Flypaper Effect Pada Dana Alokasi Umum, Dana Bagi Hasil Dan Pendapatan Asli Daerah Terhadap Belanja Daerah Pemerintah Provinsi Di Indonesia - Abrar, Naufal Muhammad Fajari; Masnila, Nelly; Dwitayanti, Yevi (Politeknik Negeri Ambon, 2024)
Examining how the Flypaper Effect, the General Allocation Fund, the Revenue Sharing Fund, and Regional Original Income affect regional expenditure in Indonesian provinces was the primary goal of this study. The researchers in this study used purposive sampling to choose 22 out of 38 provinces in Indonesia for their investigation. The research included the years 2019 through 2022. The investigation's secondary data sources were compiled using the documentation technique. Data from the